Brain drain tax vs. brain gain benefits: General thoughts from a Spanish perspective - Báez Moreno Andrés; López Hugo López (Anali Pravnog Fakulteta u Beogradu)
One might expect that tax benefits introduced by certain developed countries to attract foreign high-skilled workers would run contrary to taxes aimed at the alleviation or deterrence of so-called brain drain. This article shows, however, that this is not necessarily the case: brain gain benefits might be justified by the existence of home-state brain drain taxes and, at the same time, serve to alleviate international double taxation generated by this type of taxes.